Improving the English Skills of Dance Students through English Learning with a Cooperative Learning Approach - Sutiyono Sutiyono; Wenti Nuryani; Puspitorini Puspitorini; Titik Putraningsih (JOURNAL OF EDUCATION, 2012)
This study was aimed at improving the habits and courage of dance students in communicating in English. This study was classroom action research with a cooperative learning approach performed through English learning in the Curriculum Review and Development Course, The research subjects were 44 students of  the Dance  Education  Department, Language  and  Art  Faculty, Yogyakarta  State University. The learning activity was Numbered Heads Together. Action  implementation was performed in 2 cycles, which were.' (1) improving the habits to ask and read texts, and (2)  improving courage to do presentation and write. Research results showed that the Numbered Heads Together strategy could motivate dance students to be active in the classroom and improve courage to communicate in English (48%  to 75% in the first  and 98% in the second cycle).   Keywords:  English speaking skills, cooperative learning, classroom technique